Pull-Type Radiologically Inserted Gastrostomy: An Improvised Technique Using a Frugal Innovation - Chahal, Anurag; Malla, Sundeep; Dash, Chinmaya; Gupta, Deepak; Gamanagatti, Shivanand (Journal of Clinical Interventional Radiology ISVIR, 2019)
Purpose To describe a new technique for “pull type” radiologically inserted gastrostomy (RIG) and prospectively compare it with conventional (described) technique in terms of technical ease (fluoroscopy time, radiation dose) and safety profile.Materials and Methods Adult patients with head injury with Glasgow coma scale (GCS) (M score) < 5, one week after decompression or those requiring nutritional support for > 4 weeks, or patients with recurrent aspiration pneumonitis on nasogastric feeding were included. Hemodynamically unstable patients or those with uncorrectable coagulopathy were excluded. Patients underwent pull-type RIG with alternate patient getting allocated to groups A (conventional technique) and B (new technique). The authors compared the technical success, complication rate, fluoroscopy time, radiation dose, and cost of hardware in these two groups.Results The average fluoroscopy time for group A (9 patients) was 498.7 ± 145.3 seconds, whereas for group B (16 patients), it was 302.8 ± 54.1 seconds with p-value = 0.06. The mean radiation dose of group A was 74.7 ± 15.7 mGy, whereas for group B, it was 56.7 ± 14.1 mGy (p-value = 0.004). The minor complication rates were 11.1% in both the groups.Conclusion The authors’ innovative technique using a customized snare has the potential to increase the technical ease of pull-type RIG with reduced fluoroscopy time, radiation dose, and cost with a similar safety profile.
Keywords: gastrostomy; traumatic brain injury; frugal innovation; pull-through gastrostomy